2020
DOI: 10.20339/am.10-20.023
|View full text |Cite
|
Sign up to set email alerts
|

Study of dynamics of value systems of youth’s leaders under pedagogical conditions of value-motivational development

Abstract: Presented is study in the problem of leadership in youth environment, in frames of which theoretical analysis of scientific works was conducted. The analysis showed, that the most actual in the present time is the value approach to leadership development for verification of which is experimental study is conducted. Results of the experiment showed dynamics of changes in values systems of both girls and boys during the period of conducting psycho-pedagogical program of values development. The analysis of experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To analyze the dynamics of changes in the indicators of values and creative thinking, a comparative analysis was carried out using the statistical Student's t-test. This analysis showed that in the control group of boys and girls, statistical differences in indicators before and after the experiment were not found (Oshchepkov & Friauf, 2020b) (Table 1). Creative thinking level.…”
Section: Resultsmentioning
confidence: 91%
“…To analyze the dynamics of changes in the indicators of values and creative thinking, a comparative analysis was carried out using the statistical Student's t-test. This analysis showed that in the control group of boys and girls, statistical differences in indicators before and after the experiment were not found (Oshchepkov & Friauf, 2020b) (Table 1). Creative thinking level.…”
Section: Resultsmentioning
confidence: 91%